South African inflation response to fiscal policy shocks - Eugene Msizi Buthelezi (Journal of Applied Economics, 2024)
The research employs Bayesian Vector Autoregressions with hierarchical priors to analyze the intricate economic implications of fiscal policy shocks on inflation, monetary policy, and fiscal authorities in the context of South Africa. The study explores data spanning from 1979 to 2022. Contrary to conventional economic theories, our analysis demonstrates that unexpected increases in national government expenditure led to counterintuitive initial decreases in inflation. This highlights the complexity of inflation dynamics and challenges existing paradigms. Moreover, the lagged response of inflation to changes in government revenue emphasizes the role of inflation expectations and market dynamics. Clear communication by fiscal authorities is crucial for shaping these expectations and understanding their impact on inflation.
Keywords: 330; Bayesian vector autoregressions; fiscal policy; Fiscal theory of the price level; hierarchical prior